Recent trends in public administration - Dubhashi, P R (Delhi, 1995)
The collection of papers under the title "Recent Trends in Public Adminis- tration" deals with a whole range of issues relating to Public Administration which has a crucial role to play in mod- ern India. These papers are classified into six parts viz. general, policy making, bureaucracy, training, politics, administration and public interest and administration of public enterprises.
Keywords: Public administration